An electronically conductive 3D architecture with controlled porosity for LiFePO4 cathodes - Nguyen, Martin; Liang, Zhiming; Garman, Kaitlin; Wang, Yangyang; Gestos, Adrian; Mo, Michael; Ban, Chunmei (Frontiers in Materials, 2023)
Thick LiFePO4 (LFP) cathodes offer a promising solution to increasing the areal capacity and reducing cost of Li-ion batteries while retaining the qualities intrinsic to LFP. Including long cycle lifetimes and thermal stability required for electric vehicles and stationary energy storage applications. However, the primary challenges of thick LFP cathodes are poor rate capability and cycling stability due to LFP's electronically insulating material property, poor electronic conductivity, and long diffusion length at high electrode thicknesses. Herein, we propose an electrode architecture composed of vertically aligned carbon fibers (CFs) attached to a plasticized current collector (PCC) to promote rate capability, cycle life, and further enhance safety of thick LFP cathodes. The effectiveness of the CF-PCC architecture is demonstrated by electrochemical analysis with a good areal capacity of 3.5 mA cm -2 , excellent cycling stability at C/3, and good rate capability up to 1C. These results are confirmed by investigating the architecture's impact on ionic diffusivity via electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) and compared to the conventional slurry cast LFP cathode.